2013
DOI: 10.7467/ksae.2013.21.4.153
|View full text |Cite
|
Sign up to set email alerts
|

Study on the Apply Characteristics to the Gasoline Engine of Exhaust Heat Recovery Device Counterflow

Abstract: : The purpose of this study is to investigate the performance characteristics of the counterflow exhaust heat recovery device for the applied gasoline engines. The EHRS device is installed behind the catalyst. This study investigates the engine warm-up characteristic, the exhaust noise characteristic, the back-pressure characteristic . The engine warm-up characteristics is (load 0%, load 10%, load 20%) in (idle, 1000rpm, 1500rpm, 2000rpm, 2500rpm) conditions by measuring the time it warmed up, coolant temper… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2016
2016
2018
2018

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 4 publications
0
1
0
Order By: Relevance
“…Park et al [5] experimentally conducted the effects of warm-up performance of the gasoline engine with the circular flow typedEHRS. They showed that under engine high load condition, the remarkable heat recovery efficiency improvement was observed.Shin et al [6] investigated the performance characteristics of the counter flow typed EHRS, such as warm-up, the exhaust noise and the back pressure of the for the gasoline engine. The warm-up period of the engine with the EHRS was shorted for the engine test conditions except at idle condition, although the back pressure wasslightly increased.…”
Section: Introductionmentioning
confidence: 99%
“…Park et al [5] experimentally conducted the effects of warm-up performance of the gasoline engine with the circular flow typedEHRS. They showed that under engine high load condition, the remarkable heat recovery efficiency improvement was observed.Shin et al [6] investigated the performance characteristics of the counter flow typed EHRS, such as warm-up, the exhaust noise and the back pressure of the for the gasoline engine. The warm-up period of the engine with the EHRS was shorted for the engine test conditions except at idle condition, although the back pressure wasslightly increased.…”
Section: Introductionmentioning
confidence: 99%